Home Environmental Factors with the Presence of Disease-Transmitting Vectors in Traditional Villages, North Lombok, West Nusa Tenggara - Nur Alvira Pascawati (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2023)
Indonesia is an archipelagic country that has many tribes and traditional villages. This makes the variables that affect the breeding and production of disease-transmitting mosquito vectors very complex. This study aims to observe customary areas that still adhere to customs in arranging community-housing patterns that may have the potential for mosquito-borne diseases. This study used a cross-sectional design with a sample of 67 houses in Segenter Hamlet. Sampling technique with the simple random sampling method. Data analysis, namely univariate, bivariate, and multivariate. The presence of disease-transmitting mosquitoes in traditional villages was mostly found in traditional-type houses. The determinant factor that contributes 77.79% to the presence of disease-transmitting mosquitoes is the placement of the kitchen outside the home. This factor is reinforced by the presence of a food storage area, the absence of an insulating door in the house, the location of the bathroom outside the house, the roof of the house made of woven, the traditional type house, the mixed type house and the walls of the house made of woven. These findings contribute to the development of an early warning system for the potential spread of vector-borne diseases and the development of health tourism through house screening.